2019
DOI: 10.1111/1471-0528.15914
|View full text |Cite
|
Sign up to set email alerts
|

Geographic variation in the use of lymphadenectomy and external‐beam radiotherapy for endometrial cancer: a cross‐sectional analysis of population‐based data

Abstract: Objective To quantify geographic variation in the use of lymphadenectomy and/or external-beam radiotherapy (EBRT) for endometrial cancer in England.Design Cross-sectional analysis of population-based data.Setting English cancer registry data, linked to chemotherapy, radiotherapy and hospital episodes statistics data.Population Twenty-two thousand four hundred and eighty-three women with endometrial cancer presenting without clinical or radiological evidence of distant metastatic spread, diagnosed in England fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Henson et al 14 used the RTDS to investigate sociodemographic variation in the use of chemotherapy and radiotherapy in patients diagnosed with stage IV lung, oesophageal, stomach and pancreatic cancer. White et al 15 used the RTDS to quantify geographic variation in the use of lymphadenectomy and external beam radiotherapy for endometrial cancer in England. Morris et al 16 showed that wide variation exists in the use and type of radiotherapy delivered in the management of rectal cancer across the English NHS.…”
Section: Findings To Datementioning
confidence: 99%
“…Henson et al 14 used the RTDS to investigate sociodemographic variation in the use of chemotherapy and radiotherapy in patients diagnosed with stage IV lung, oesophageal, stomach and pancreatic cancer. White et al 15 used the RTDS to quantify geographic variation in the use of lymphadenectomy and external beam radiotherapy for endometrial cancer in England. Morris et al 16 showed that wide variation exists in the use and type of radiotherapy delivered in the management of rectal cancer across the English NHS.…”
Section: Findings To Datementioning
confidence: 99%